Analisis Etos Kerja Pedagang Sayur Keliling Perempuan Di Kabupaten Probolinggo - Kholifatul Fiardillah; Avinda Diana Rahiliah; Rohmawati Rohmawati (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
This study aimed to determine the work ethics of women mobile vegetable traders in business operations in Probolinggo district, more specifically in Paiton and Pakniran districts, and to determine the impact of work ethics of women mobile vegetable traders on business income. It was carried out as a purpose. Vegetable seller in Probolinggo area. The type of research used in this study is qualitative. The sample used in the study consisted of her 10 people and non-probability sampling and purposive sampling were used. The researchers used observation and interview techniques to obtain information from all respondents in the Probolinggo district. The findings show that female vegetable mobile vendors in Probolingo Regency have a good work ethic in running their businesses. And work ethics has a positive and significant impact on the increase in economic income of mobile vegetable traders in Probolinggo district.